2017
DOI: 10.29173/iq6
|View full text |Cite
|
Sign up to set email alerts
|

Journals in Economic Sciences: Paying Lip Service to Reproducible Research?

Abstract: The findings of numerous replication studies in economics have raised serious concerns regarding the credibility and reliability of published applied economic research. Literature suggests that economic research often is not replicable because (i) only a small proportion of journals in the field have implemented functional policies on the disclosure of employed datasets and program code, (ii) authors frequently do not comply with these data policies and (iii) editorial offices do not ensure that these policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Superficial engagement with open research practices (such as underspecifying a pre-registered study) can also be used to mislead readers and reviewers about the strength of research (device 19; open research washing). For instance, one study of data availability in economics found that only 47.5% of articles in journals with a data-availability policy actually complied with the policy ( Vlaeminck and Podkrajac, 2017 ; see also Tedersoo et al, 2021 ).…”
Section: A Tentative Typology Of Persuasive Communication Devicesmentioning
confidence: 99%
“…Superficial engagement with open research practices (such as underspecifying a pre-registered study) can also be used to mislead readers and reviewers about the strength of research (device 19; open research washing). For instance, one study of data availability in economics found that only 47.5% of articles in journals with a data-availability policy actually complied with the policy ( Vlaeminck and Podkrajac, 2017 ; see also Tedersoo et al, 2021 ).…”
Section: A Tentative Typology Of Persuasive Communication Devicesmentioning
confidence: 99%
“…Of those 58 journals, 34 had a mandatory policy (58.6%). Chang and Li (2015) and Vlaeminck and Podkrajac (2017) have examined how voluntary and mandatory data policies perform. The authors concluded that mandatory data policies perform better, because the probability to find the data necessary to conduct reproductions is higher than for journals with voluntary data policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on openwashing shows that at least some of the initiatives using the branding of "open" do not meet the criteria that most open education advocates would advance [22,23]. In the interest of retaining a critical perspective, it is fair to ask in whose interest "openness" operates [24]. At the least, we must be circumspect about grand claims of decolonisation through OER.…”
Section: Introductionmentioning
confidence: 99%